NPAsym: an open-source plugin for ImageJ to quantify nuclear shape asymmetry. (November 2020) - Bozhok, Y.M.; Golovko, O.; Nikonenko, A.G.
Highlights: Symmetry is an important aspect of nuclear shape not receiving the attention it merits. A software, nPAsym, implemented as ImageJ plugin is presented allowing to measure nuclear shape asymmetry in digital images captured from cytologic and histologic preparations. nPAsym has proved itself effective in distinguishing between some of the nuclear shape phenotypes. nPAsym has a potential to become useful for both experimental research and diagnostics. Abstract: Background and objectives: : The nucleus is a complex and dynamic organelle enclosing the major part of the cell's genome. A growing body of evidence suggests that changes in the shape of this organelle can influence cell activities. The other way around, altered nuclear shape may be indicative of impaired cell function. Symmetry is an important aspect of nuclear shape not receiving the attention it merits. We address this problem by presenting a software tool allowing to quantify nuclear shape asymmetry in light microscopy images. Methods: : The software named nPAsym is written in Scala and implemented as a plugin to ImageJ making possible to use it in combination with other ImageJ tools. The plugin works with 8-bit images segmented into black nuclear masks and white background. It performs a number of operations allowing to analyze multiple objects within a single image, removing some segmentation artefacts, filtering out objects incomplete and below a specified size. The feature of interest is quantified using the notion of point asymmetry. The performance of nPAsym was tested in a small-scale study comparing nuclear shapes for cells of nodular goiter, follicular thyroid adenoma and papillary thyroid carcinoma. Results: : We present nPAsym, the ImageJ plugin, that measures nuclear shape asymmetry. It works with digital microscopic images segmented using either a raster graphics editor or built-in ImageJ functions. nPAsym is packaged in a single .jar file and does not require installation as well as configuration. It has proved effective in distinguishing between some of the nuclear shape phenotypes. Conclusions: : nPAsym is the user-friendly, platform-independent and open-source software tool allowing to quantify nuclear shape asymmetry in digital images captured from cytologic and histologic preparations. It has a potential to become useful for both experimental research and diagnostics.